التّشويق في السّرد العربيّ المعاصر تجربة جعفر العقيلي السّرديّة أنموذجًا دراسة في جماليّات التّأثير والتّلقّي - الصعيدي, ميادة انور (University of El-oued, 2021)
الملخّص: يعدّ التشويق من أهمّ العوامل التي تجعل العمل الفنّيّ مقروءًا، فإن أتقن الكاتب بثّه في قصّه، بوصفه مصدرًا للمعرفة، وموجّهًا للسلوك والأخلاق، ومفجّرًا لقدرة التخيّل، وحافزًا على توقّع الأحداث، ومنميًّا للثروة اللغويّة، فقد حقّق من خلاله الإمتاع والإقناع معًا. ويتوقّف مدى إحداث التشويق على كيفيّة نزع الصورة المألوفة للغة القارئ، بحيث يدفعه إلى أن يعيش صدمة المسافة بين ما يعرفه وما يكتشفه، فضلًا عن الأساليب والتّراكيب المبتكرة، ومن هنا فقد خصّص جعفر العقيلي أدواتٍ عاليةَ الجودة، ومهاراتٍ فنّيّةً مستحكمةً في قصصه؛ تثير وجدان القارئ، وتعبث في وعيه الفكريّ، إذ تجلّى التّشويق كأسلوب جماليّ مذّ عتبات القصّ حتّى الأثر "ما بعد القراءة". Abstract: The excitement factor is what makes the art work legible, so if the writer mastered its transmission in his story, so that it is a source of knowledge, a guide to behavior and morals, a trigger for the ability of imagination, a catalyst for anticipating events, and a stimulus for the linguistic wealth, then he has achieved both amusement and persuasion. The extent of the suspense creation depends on how the familiar image of the reader's language is stripped, forcing him to live the shock of the distance between what he knows and what he discovers, as well as innovative methods and combinations. Hence, Al-Aqili has devoted high-quality tools to his stories. It arouses the reader's consciousness and messes with the rest of his thought, as the suspense manifested itself as an aesthetic method from the thresholds of the storytelling to the effect "after reading".
The Excitement In Contemporary Arabic Storytelling Jafar Al-aqili's Story Experience As A Model A Study In The Aesthetics Of Influence And Reception
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج04. ع.02. جامعة الوادي
Keywords: لتّشويق، القصّ، جعفر العقيلي، جماليّات، التّلقّي; suspense, storytelling, Jaafar Al-Aqili, aesthetics, reception